An Analysis of Errors in Present Indefinite Tense Sentences: A Case of 6th Grade ESL Learners of Sialkot, Pakistan - Naz, Waheedah; Safarish, Anum; Syed, Ali Furqan; Jabbar, Shanza; Nawaz, Ayesha (Journal of Education and Social Studies, 2023)
Reading the piece of writings in the target language is also suggested to enhance creative ability, while the basic tenets of English Grammar can also be improved through a comparative study of the grammatical concepts. The study aims to identify, discuss, explain, and categorize the grammatical errors, especially errors in present indefinite tense sentences committed by the ESL learners of 6th grade at Cantt Public High School, Sialkot, Pakistan, due to overgeneralization in written exercises. The study gathered data through a worksheet task comprising 10 items of translation sentences from Urdu to English and ten items of English fill-in-the-blanks comprised of grammatical use of present simple tense and agreement morpheme. Corder’s model (1967) of error analysis has opted to analyze the errors in the present indefinite tense. This study pays great attention to overgeneralization in Present Indefinite tense sentences of ESL learners of 6th grade. The learners overgeneralize in the use of rules used for verb forms and auxiliary verbs. The present study also found that a lack of knowledge of the rules of the target language, in addition, to overgeneralization, is the cause of such errors, for instance, the inappropriate use of prepositions. The findings suggest that teachers of English should focus their attention on the troublesome aspect of the present simple tense while also encouraging students to apply the drill practice to the study of the present indefinite tense. This study has a few limitations as it was not feasible for researchers to analyze all kinds of tenses and find all types of errors according to the opted model due to time restraints.